2011
DOI: 10.1002/mabi.201000456
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Efficacy of Doxorubicin Released from Crosslinked Nanoparticulate Chondroitin Sulfate/Chitosan Polyelectrolyte Complexes

Abstract: It is demonstrated that nanoparticulate PEC with a crosslinked shell sustains DOX release and increases DOX activity against cancer cells. CSMA was synthesized to prepare PEC with chitosan. The double bonds among CSMA were used to form a shell crosslink. The released DOX from DOX-loaded PECs against human cancer KB cells and A549 cells were qualitatively traced by confocal laser scanning microscopy and flow cytometry, and quantitatively measured by capillary electrophoresis. All the results implied the DOX-loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 33 publications
(28 reference statements)
0
28
0
Order By: Relevance
“…23 Tsai et al produced doxorubicinencapsulated Cs-ChS nanoparticles that were applied against cancer cells. 24 However, to our knowledge, our study marks the first time the construction of a Cs-ChS based system for AmpB delivery has been developed for the treatment of leishmaniasis.…”
Section: Introductionmentioning
confidence: 92%
“…23 Tsai et al produced doxorubicinencapsulated Cs-ChS nanoparticles that were applied against cancer cells. 24 However, to our knowledge, our study marks the first time the construction of a Cs-ChS based system for AmpB delivery has been developed for the treatment of leishmaniasis.…”
Section: Introductionmentioning
confidence: 92%
“…CTS/CS nanoparticles were prepared according to the ionic gelation method described by Tsai et al [11] with minor modifications. The colloidal suspension of CTS/CS nanoparticles was obtained through the electrostatic interaction between a solution of CTS at pH 4.0, 5.0 and 6.0 (solution concentration: 0.2% in acetic acid 0.2 mol L −1 ) and CS (solution concentration: 0.15% in acetic acid 0.1 mol L −1 ).…”
Section: Preparation Of Cts/cs Nanoparticlesmentioning
confidence: 99%
“…Polyelectrolyte complexes formed by interaction between the CTS and the CS have the advantage of being an ideal matrix for various biomedical applications, since they have higher chemical and mechanical stabilities [9][10][11]. Nanoparticles based on CTS/CS have been cited in the literature for drug encapsulation, such as doxorubicin [11], but there are no reports of the use of this system for the nanoencapsulation of curcumin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al, (2007), who examined the release of bovine serum albumin (BSA) and 684 R6G (Rhodamine 6G) from chitosan/dextran sulphate NPs in PBS with different ionic strength 685 also observed that the greatest release of both proteins occurred in the release media of a high 686 28 ionic strength. Sustained release of BSA and doxorubicin from CHON/chitosan polyelectrolyte 687 NPs was reported by Yeh et al (2011) andTsai et al (2011), respectively, with evidence that BSA 688 release properties were pH sensitive. Release of sCT from CHON/PROT MMR=4.2 NPs was 689 comparable to those from CHON/PROT MMR=6.3 (data not shown), it may be concluded that 690 release of the loaded bioactive from CHON-based NPs is influenced mainly by the peptide 691 interactions with the polyanion (CHON) and not with the polycation.…”
mentioning
confidence: 79%